Sumoylation: a regulatory protein modification in health and disease - Flotho, Annette; Melchior, Frauke (Annual review of biochemistry, 2013)
Posttranslational modification with small ubiquitin-related modifier (SUMO) proteins is now established as one of the key regulatory protein modifications in eukaryotic cells. Hundreds of proteins involved in processes such as chromatin organization, transcription, DNA repair, macromolecular assembly, protein homeostasis, trafficking, and signal transduction are subject to reversible sumoylation. Hence, it is not surprising that disease links are beginning to emerge and that interference with sumoylation is being considered for intervention. Here, we summarize basic mechanisms and highlight recent developments in the physiology of sumoylation.